Performance comparisons of the soft computing algorithms in lung segmentation and nodule identification - Khanum, Afshan; Purushothaman, S.; Rajeswari, P. (International Journal of Engineering and Technology, 2017)
This paper presents the implementation back propagation algorithm (BPA) and fuzzy logic(FL) in lung image segmentation and nodule identification. Lung image database consortium (LIDC) database images has been used. Features are extracted using statistical methods. These features are used for training the BPA and FL algorithms. Weights are stored in a file that is used for segmentation of the lung image. Subsequently, texture properties are used for nodule identification.